Evaluation of Sewage Wastewater Quality: Physico-Chemical and Microbiological Analysis in Khammam City, Telangana - B.Lalitha Kumari (The Bioscan, 2021)
This study was conducted to findout the physico-chemical and microbiological parameters were analyzed in city waste water of Khammam city Telangana. This water has different pollution parameters i.e., Organic pollutants like dissolved oxygen, bio-chemical oxygen and chemical oxygen demand,Free carbon dioxide, organic matter, In-organic pollutants-electrical conductivity, turbidity, pH , total alkalinity, chloride, etc.,Temperature range from 23oC to 33oCThe minimum and maximum pH range from 6.4 to 7.4. The minimum and maximum total alkalinity range from 42 mg/L to 154 mg/L, The minimum and maximum chloride from 136.9 to 278.9 mg/Lwere found. Eutrophic factors like phosphates, nitrates, nitrites were analyzed. The microbiological parameters, total coliform bacteria, fungi, actinomycetes colonies were also analyzed. the effects of disease on a worldwide scale, methodological advancements are required.